Strategies and boundaries: Subcontracting in construction - Üsdiken, Behlül; Sözen, Zeynep; Enbiyaoḡlu, Hayat (Strategic Management Journal, 1988)
Abstract A central concern in studying organization environment relationships has been the issue of how boundaries of organizational activity are defined and altered. A specific organizational response that pertains to the issue of boundaries is subcontracting. Construction is one industry where subcontracting is used extensively. Eccles' (1981a) study shows, however, that there is great variation in the subcontracting practices of contractors. This paper reports an exploratory study on the possible determinants of the extent of subcontracting by the construction firm.